Amoxicillin and clavulanate potassium related Leucocytoclastic vasculitis - Snehal Balvant Lunge; Vijaya Sajjan; Ashok M. Pandit; B.S. Manjunathswamy; Anshul Agrawal; Shivakumar Patil (Our Dermatology Online, 2014)
Leukocytoclastic vasculitis (LCV) is a small-vessel vasculitis with a reported incidence rate of 30 cases per million persons per year. It usually presents as a palpable purpuric skin rash on legs, though any part of the body can be affected. LCV rash may have an associated burning sensation or pain and in some cases may involve internal organs. In some cases, LCV rash may present as nodules, recurrent ulcerations or asymptomatic lesions. The diagnosis of LCV is usually made on skin biopsy. Etiological triggers may not be identified in as many as half of the cases. Treatment is usually conservative and includes identification and removal or treatment of the etiological trigger except in cases with internal organ involvement where systemic steroids and immunosuppressant may be necessary. In this article we present a case of Amoxicillin and Clavulanate potassium associated LCV that improved with discontinuation of the offending agent and treatment with systemic corticosteroids.